2020
DOI: 10.1016/j.psj.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese and Bacillus subtilis on the reproductive performance, egg quality, antioxidant capacity, and gut microbiota of breeding geese during laying period

Abstract: This experiment was conducted to investigate the effects of manganese ( Mn ) and Bacillus subtilis ( BS ) on the production performance, egg quality, antioxidant capacity, and gut microbiota of breeding geese during laying period. A total of 120 forty-six-week-old breeding geese (Wulong) were randomly assigned to 1 of 6 treatment diets formulated to supply 10, 20, and 30 mg/kg Mn with 5 × 10 9 CFU/kg or 2.5 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…The addition of B. subtilis has been reported to play a positive effect on antioxidant activity of broilers ( Bai et al, 2018 ; Xu et al, 2021 ). Here, we found that 5 × 10 9 CFU/kg B. subtilis supplementation increased the T-AOC in serum of laying geese breeders, in agreement with our previous study ( Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…The addition of B. subtilis has been reported to play a positive effect on antioxidant activity of broilers ( Bai et al, 2018 ; Xu et al, 2021 ). Here, we found that 5 × 10 9 CFU/kg B. subtilis supplementation increased the T-AOC in serum of laying geese breeders, in agreement with our previous study ( Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Studying the animal gut microbiota, Moeller et al (2018) reported that the composition of gut microbiota was different among animals. There are extremely significant differences among the diversity and richness of gut microbiota of horses ( Mshelia et al, 2018 ), rats ( Rolim et al, 2021 ), geese ( Wang et al, 2020 ), cows ( Uchiyama et al, 2020 ), and goats ( Liu et al, 2020 ). To date, there have been only few 16S ribosomal RNA (rRNA) gene sequencing technology-based studies, which have investigated the gut microbiota of small ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…Fusobacteriaceae could modulate the growth of other bacterial species through metabolic by-products, which was helpful for the maintenance of an overall microbial structure. Similarly, Wang et al (2020) found that dietary probiotic Bacillus subtilis supplementation increased the abundances of Fusobacteria phylum, Fusobacteriia class, Fusobacteriaceae family, and Fusobacterium genus and improved the performance of breeding geese during the laying period. Lachnospiraceae was involved in the production of SCFAs (butyrate, propionate, and acetate), which were important energy sources for intestinal epithelial cells (Rychlik, 2020).…”
Section: )mentioning
confidence: 90%